1979
DOI: 10.1007/bf01477491
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunologische Bestimmung von Human-Myoglobin in der Diagnostik des akuten Myokardinfarkts

Abstract: A radioimmunoassay was developed to determine serum myoglobin (SMb). 50 healthy persons showed values between 0 and 90 ng/ml. Serial tests of 10 patients following acute myocardial infarction or during angina pectoris (AP) indicated that SMb reached pathological values before CK and CK-MB (average 250 +/- 95 ng/ml at the time of hospitalisation which corresponds to 3.3 +/- 1.4 h after beginning of angina pectoris). At hospitalisation the simultaneously determined CK was within normal limits and reached patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1980
1980
1983
1983

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…In a limited sense, it can be confirmed that the serum myo globin level is primarily higher than the described standard value in case of the following diseases: skeletal muscle damage, severe renal affection, where the secretion of the protein is delayed and elevated serum levels result. Furthermore, elevated values were observed in a traumatic rhabdomyolysis (12), a limitation which can be disregarded in the case in question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a limited sense, it can be confirmed that the serum myo globin level is primarily higher than the described standard value in case of the following diseases: skeletal muscle damage, severe renal affection, where the secretion of the protein is delayed and elevated serum levels result. Furthermore, elevated values were observed in a traumatic rhabdomyolysis (12), a limitation which can be disregarded in the case in question.…”
Section: Discussionmentioning
confidence: 99%
“…According to corresponding statements of various authors (12,18,21) the myoglobin normally circulating in blood ranges between 6 and 85 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei Muskelzellnekrosen wird neben Enzymen wie Kreatinkinase oder Laktatdehydrogenase auch Myoglobin freigesetzt. Myoglobinämie und Myoglobinurie können mit spezifischen Methoden laborchemisch erfaßt werden (8,19). Klinische Bedeutung gewinnt die Bestimmung von Myoglobin im Serum insbesondere bei der Diagnostik des akuten Myokardinfarktes (8,9,11,12) sowie beim Nachweis toxischer oder traumatischer Rhabdomyolysen (20,21).…”
unclassified
“…Myoglobinämie und Myoglobinurie können mit spezifischen Methoden laborchemisch erfaßt werden (8,19). Klinische Bedeutung gewinnt die Bestimmung von Myoglobin im Serum insbesondere bei der Diagnostik des akuten Myokardinfarktes (8,9,11,12) sowie beim Nachweis toxischer oder traumatischer Rhabdomyolysen (20,21). Obgleich seit Einführung eines spezifischen, sensitiven Radioimmunoassays (19) die Bestimmung von Serum-Myoglobin zunehmend in den Mittelpunkt klinischen Interesses rückt und zahlreiche klinische Untersuchungen bereits vorliegen (l, 27), fehlen bislang verläßliche Informationen über Verteilungscharakteristik und Normwertebereich von Serum-Myoglobin.…”
unclassified